2016
DOI: 10.2903/j.efsa.2016.4622
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of 3‐phytase FLF1000 as a feed additive for chickens for fattening and laying hens

Abstract: The additive is a preparation of 3-phytase which is produced by a genetically modified strain of Komagataella pastoris. The production strain and its recombinant DNA were not detected in the final product. Therefore, the additive does not give rise to safety concerns with regard to the genetic modification of the production strain. Based on the results of the tolerance studies provided, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) concluded that the additive is safe for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…Safety aspects regarding the use of the liquid formulation of the additive in feed for poultry species, including the safety aspects of the genetic modification, have been previously evaluated (EFSA FEEDAP Panel, 2016).…”
Section: Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…Safety aspects regarding the use of the liquid formulation of the additive in feed for poultry species, including the safety aspects of the genetic modification, have been previously evaluated (EFSA FEEDAP Panel, 2016).…”
Section: Safetymentioning
confidence: 99%
“…No studies have been conducted with 3-phytase FSF10000 to support the safety for the target species. In a previous assessment, tolerance studies done with the liquid formulation of the additive in chickens for fattening and laying hens were evaluated (EFSA FEEDAP Panel, 2016). From the results, the FEEDAP Panel concluded that the use of the liquid formulation is safe for chickens for fattening and laying hens at 1,000 FTU/kg feed.…”
Section: Safety For the Target Speciesmentioning
confidence: 99%
“…The additive 3-phytase FLF1000 in its liquid formulation contains 3-phytase (Enzyme Commission number 3.1.3.8) produced by a genetically modified strain of K. phaffii (CECT 13094) with a minimum phytase activity of 1,000 FTU/mL. In a previous opinion, the Panel described the additive and its manufacturing process including the production strain and its genetic modification (EFSA FEEDAP Panel, 2016).…”
Section: Characterisationmentioning
confidence: 99%
“…Safety aspects regarding the use of this additive in feed including the safety of the production strain, the safety for the consumer, for the users and for the environment have been previously evaluated (EFSA FEEDAP Panel, 2016). The FEEDAP Panel concluded that there are no concerns regarding the genetic modification of the production strain, that there are no concerns for the consumer safety and no risks for the environment are expected from the use of the product as a feed additive.…”
Section: Safetymentioning
confidence: 99%
“…The additive 3-phytase FLF1000 contains 3-phytase (Enzyme Commission number 3.2.1.8) produced by a genetically modified strain of Komagataella pastoris (CECT 13094) and is authorised as a feed additive for chickens for fattening and laying hens. 4 The FEEDAP Panel adopted on opinion on the safety and efficacy of the product as a feed additive for chickens for fattening and laying hens (EFSA FEEDAP Panel, 2016). The applicant is now requesting for an extension of the use of the additive to chickens reared for laying and minor poultry species (excluding minor poultry species for laying/breeding).…”
Section: Additional Informationmentioning
confidence: 99%